3D DV–hop localisation scheme based on particle swarm optimisation in wireless sensor networks. (1st December 2014) - Chen, Xiao; Zhang, Benliang
To improve the node localisation performance of the distance vector–hop (DV–hop) algorithm in the three–dimensional (3D) space, an improved range–free node localisation algorithm in the 3D wireless sensor networks is proposed by analysing the lack of the existing 3D localisation algorithms. After performing the 3D DV–hop algorithm, we use the particle swarm optimisation (PSO) algorithm with the inertia weight to emend unknown nodes' location estimated by the 3D DV–hop algorithm. The simulation results show that the proposed algorithm, in comparison with the original 3D DV–hop algorithm, greatly reduces the localisation error and error variance. It enhances the localisation precision and stability effectively without increasing the additional hardware and communication cost.